The effect of desire to be liked and social appearance anxiety on aesthetic surgery acceptance in female nurses - Yaşar Demir; Erhan Dağ; Pınar Karakuş; Zeynep Aydın Kılınç (BMC, 2024)
Abstract Background A rapid increase has been observed in aesthetic surgery procedures in recent years and it has been determined that females have more aesthetic procedures. While different groups of female groups were taken as a sample in the studies, no study on female nurses was found. In this study, it is thought that psychological reasons such as stress, anxiety, desire to be liked and lack of self-confidence that lead women to plastic surgery will reduce the professional performance of nurses and this situation will create additional workload for other colleagues. Therefore, the aim of the study is to reveal the effect of desire to be liked and social appearance anxiety on the acceptance of female nurses to plastic surgery. Methods The population of the cross-sectional study consisted of 243.565 nurses working in public, private and university hospitals in Turkey. A questionnaire form was used as a data collection tool in the study. In the first part of the form, there are statements aiming to reveal the socio-demographic characteristics, social media usage levels and aesthetic surgery experiences of nurses, and in the second part, there is a desire to be liked scale, social appearance anxiety scale and aesthetic surgery acceptance scale. The 1004 questionnaire forms collected as a result of the study were subjected to percentage, frequency, correlation and regression analysis. Results 41.2% of the nurses have had aesthetic procedures before and 68.4% of them want to have aesthetic procedures when there is an area they do not like in their body. A strong positive relationship was found between the desire to be liked, social appearance anxiety, and aesthetic surgery acceptance (r > 0.500, p < 0.01). Aesthetic surgery acceptance is affected by the desire to be liked and by social appearance anxiety. Conclusion In the study, it was determined that social appearance anxiety and the desire to be liked led female nurses to plastic surgery. According to the results of similar studies conducted in different groups, it may be recommended that awareness training be organized both in schools and through digital media about the consequences of unnecessary plastic surgery.